Unlocking E-Learning Triumph: Nurturing Support Systems and Student Traits in Secondary School Implementation - Azrul Azrul; Ulfia Rahmi (STAI Hubbulwathan Duri, 2023)
The utilisation of e-learning via the Internet provides the benefits of adaptability, extensive accessibility to educational materials, and convenient entry. Nevertheless, the utilisation of the Internet in education presents concerns like the presence of irrelevant content and potential risks to data security. The objective of this study is to obtain precise data by administering questionnaires that assess the availability of e-learning resources such as computer equipment and internet networks, user proficiency, and learner characteristics. Data were gathered via interviews conducted with teachers, observations made of e-learning enabling facilities, and the distribution of questionnaires to high school students in Pariaman City. The findings indicate that educational institutions are prepared to facilitate e-learning. The primary advantage of using E-Learning is the availability of open and widely accessible learning resources. The introduction of the E-learning system encountered issues, notably the presence of irrelevant content. Hence, the objective of this study is to uncover information pertaining to the necessary e-learning resources that facilitate the process of learning. A questionnaire was employed as the data gathering instrument. The primary concept presented in the document explores computer devices and internet networks, user functionalities, and participant and student attributes. The specimen constituted a secondary educational institution. Interviewing was another method employed for data collecting. The interview focused on eliciting information regarding the E-learning infrastructure acquired from both professors and students. The findings indicate that the school is prepared to adopt E-learning. However, the implementation of Intranet-based E-learning is necessary to address the current challenges.